2007
DOI: 10.1152/japplphysiol.00927.2006
|View full text |Cite
|
Sign up to set email alerts
|

Excessive heart rate response to orthostatic stress in postural tachycardia syndrome is not caused by anxiety

Abstract: Masuki S, Eisenach JH, Johnson CP, Dietz NM, BenrudLarson LM, Schrage WG, Curry TB, Sandroni P, Low PA, Joyner MJ. Excessive heart rate response to orthostatic stress in postural tachycardia syndrome is not caused by anxiety.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
50
0
4

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 83 publications
(56 citation statements)
references
References 37 publications
(43 reference statements)
2
50
0
4
Order By: Relevance
“…11 Patients complain of poor exercise tolerance with physiological features including reduced stroke volume and reflex tachycardia typical of subjects who are deconditioned, such as in persons who have had prolonged bed rest. 15 Coupled with the poor exercise tolerance, an excessively long recovery cycle following exercise is often described. Additionally, patients typically note that they have low energy, even at rest.…”
Section: Clinical Featuresmentioning
confidence: 99%
See 1 more Smart Citation
“…11 Patients complain of poor exercise tolerance with physiological features including reduced stroke volume and reflex tachycardia typical of subjects who are deconditioned, such as in persons who have had prolonged bed rest. 15 Coupled with the poor exercise tolerance, an excessively long recovery cycle following exercise is often described. Additionally, patients typically note that they have low energy, even at rest.…”
Section: Clinical Featuresmentioning
confidence: 99%
“…We concluded that although anxiety is commonly present in POTS, the HR response to orthostatic stress in POTS patients is not caused by anxiety, but is a physiological response that maintains arterial pressure during venous pooling. Masuki et al 15 studied 13 patients with mild POTS and 10 matched controls. Exercise was associated with a greater elevation in HR in POTS patients, especially while upright, was secondary to reduced stroke volume, and was associated with poor exercise tolerance.…”
Section: Pots With Deconditioningmentioning
confidence: 99%
“…They insisted that a more comprehensive treatment for POTS would better treat her illness. Unfortunately, patients with POTS are overly characterized as being anxious, and their anxiety is viewed as the driving force rather than one component of the overall illness [2,5]. Several studies have examined anxiety in patients with POTS.…”
Section: Literature Review and Case Discussionmentioning
confidence: 99%
“…Masuki et al sought to better understand the relationship between POTS and anxiety [5]. In a group of fourteen patients with POTS and ten healthy controls, all subjects underwent heart rate monitoring during lower-body negative pressure (LBNP), simulating an orthostatic increase in lower extremity venous pooling, and mental arithmetic tests to represent an anxiety-provoking stimulus.…”
Section: Literature Review and Case Discussionmentioning
confidence: 99%
“…Muchas de las actividades de la vida diaria pueden estar interferidas por las molestias 8,9 . Los pacientes clásicamente no consultan mé-dico por mucho tiempo o son erróneamente diagnosticados como depresión, estrés, fatiga crónica o trastorno de pánico 7,10 , se quejan de fatiga extrema, intolerancia al ejercicio, mareos, disminución de la concentración y síncopes [1][2][3][4][5][6][7][8] . En el Laboratorio de Estudios Autonómicos de nuestro Hospital, hemos estudiado 15 casos en los que la taquicardia ortostática ocurre dentro de los primeros 10 minutos al ponerse de pie, cumpliendo por lo tanto la defi nición [1][2][3] .…”
unclassified